Structural features of protic ionic liquids and their impact on pretreatment performance for 2G ethanol production - Pin, Thaynara C.; Nakasu, Pedro S.Y.; Rabelo, Sarita C. [UNESP]; Costa, Aline C. (Elsevier, 2021)
Biomass pretreatment with protic ionic liquids (PILs) is a promising source of renewable energy and bioproducts, in which different cation/anion combinations may present different behavior towards biomass modification such as selective lignin and/or carbohydrate solubilization. The potential of 20 PILs as pretreatment agents was investigated, whose cations presented two different functional groups and different carbon chain lengths. The best solvent in terms of lignin solubilization during pretreatment was obtained by cations with a functional group (-OH and –NH2). High cellulose conversion was obtained with ethanolamine and ethylenediamine monoacetate ([2He][Ac] and [Etid][Ac]), under different pretreatment conditions (175 °C and 140 °C for 2 h, respectively). The presence of an alkaline anion and a functionalized cation enhanced the pretreatment effectiveness. The results presented in this work will be useful to design novel protic ionic liquids for pretreatment applications in biofuel processes, which can also be integrated to produce bioproducts within the biorefinery concept.
Keywords: Cation chain length; Cation-functionalized; Enzymatic hydrolysis; Lignocellulosic biomass